Try NerdPal! Our new app on iOS and Android

# Solve the equation $5t-3=18+3\left(1-t\right)$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$t=3$
Got another answer? Verify it here

## Step-by-step Solution

Problem to solve:

$5t-3=18+3\left(1-t\right)$

Choose the solving method

1

Multiply the single term $3$ by each term of the polynomial $\left(1-t\right)$

$5t-3=18+3-3t$

Learn how to solve one-variable linear equations problems step by step online.

$5t-3=18+3-3t$

Learn how to solve one-variable linear equations problems step by step online. Solve the equation 5t-3=18+3(1-t). Multiply the single term 3 by each term of the polynomial \left(1-t\right). Add the values 18 and 3. We need to isolate the dependent variable t, we can do that by subtracting -3 from both sides of the equation. Grouping terms.

$t=3$
SnapXam A2

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Tips on how to improve your answer:

$5t-3=18+3\left(1-t\right)$

### Main topic:

One-variable linear equations

~ 0.04 s